Out-of-pocket expenses and rationing of insulin and diabetes supplies: findings from the 2022 T1International cross-sectional web-based survey - Souris, Katherine Janine; Pfiester, Elizabeth; Thieffry, Axel; Chen, Yanbing; Braune, Katarina; Kapil Bhargava, Mridula; Samra, Ravjot; Gómez, Pilar; O'Donnell, Shane (Frontiers in Clinical Diabetes and Healthcare, 2024)
IntroductionContinue investigating Out-of-Pocket Expenses (OoPEs) and rationing of insulin and diabetes supplies, including impacts of the COVID-19 pandemic, for people with type 1 diabetes (T1D).MethodsA cross-sectional web-based survey was conducted in English and advertised by T1International’s global network of patient advocates from May through September 2022. Participants provided monthly OoPEs and rationing frequency for insulin and supplies, impacts of the COVID-19 pandemic, and open-ended comments.ResultsIn the seven most represented countries, mean monthly OoPEs were highest in the United States, followed by Panama, Canada, and India, and were much lower in the United Kingdom, Germany, and Sweden. OoPEs were highest for participants with partial healthcare coverage, followed by those with no healthcare coverage. The COVID-19 pandemic negatively impacted access and/or affordability of insulin and/or supplies for over half of participants. Globally, 19.5% reported insulin rationing and 36.6% reported rationing glucose testing supplies. Qualitative analysis of open-ended responses identified themes such as ‘mental health impacts’ and ‘limits to life choices.’DiscussionHigh OoPEs lead to rationing of insulin and supplies for many people with T1D globally. Healthcare systems improvements and price reductions of insulin and supplies are needed to ensure adequate, equitable access for all.